If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -6) + -8(x + 2) = -10 Reorder the terms: 6(-6 + x) + -8(x + 2) = -10 (-6 * 6 + x * 6) + -8(x + 2) = -10 (-36 + 6x) + -8(x + 2) = -10 Reorder the terms: -36 + 6x + -8(2 + x) = -10 -36 + 6x + (2 * -8 + x * -8) = -10 -36 + 6x + (-16 + -8x) = -10 Reorder the terms: -36 + -16 + 6x + -8x = -10 Combine like terms: -36 + -16 = -52 -52 + 6x + -8x = -10 Combine like terms: 6x + -8x = -2x -52 + -2x = -10 Solving -52 + -2x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '52' to each side of the equation. -52 + 52 + -2x = -10 + 52 Combine like terms: -52 + 52 = 0 0 + -2x = -10 + 52 -2x = -10 + 52 Combine like terms: -10 + 52 = 42 -2x = 42 Divide each side by '-2'. x = -21 Simplifying x = -21
| 6x-15=9+3x | | 13x+17y=19 | | 2x+10=6+4x | | -7(x+4)+4x+7=8x+6 | | 7/60=a | | 2x-16=-128 | | 1.4(x)=2x-3 | | 2/5*7/-6*-7=a | | .5(x)=2x-3 | | x+18=106 | | 2/5*7/-6*-7 | | -1(x)=2x-3 | | 1(x)=2x-3 | | 4/-6+2=-1 | | 3(x)=2x-3 | | 3(6x-4)-4(x+7)=6x-96+x | | 4(4x+1)=3x-4(6-x)8 | | 2.75(x)=2x-3 | | -7(x-2)=-4 | | 0.86=exp(-6.2831*f) | | 0.86=exp(-2*pi*f) | | (3x-2)2=(2x+3)2 | | 9^4x*27^2-3x=1/9 | | x^5x^7/x^6 | | 5-2q=3Q | | 6(4+2x)-(8x-22)=68 | | X^2+0.2x-0.48=0 | | 3(-6)+2y=6 | | -6(x-2)+4(5n-3)=-36 | | 4(b+1)=-2(b+2) | | 8+x-1/x+4 | | -5-2(-6)=7 |